2011
DOI: 10.4061/2011/805795
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of Enzymatically DelignifiedBambusa bambosfor Efficient Hydrolysis at Minimum Cellulase Loading: An Optimization Study

Abstract: In the present investigation, Bambusa bambos was used for optimization of enzymatic pretreatment and saccharification. Maximum enzymatic delignification achieved was 84%, after 8 h of incubation time. Highest reducing sugar yield from enzyme-pretreated Bambusa bambos was 818.01 mg/g dry substrate after 8 h of incubation time at a low cellulase loading (endoglucanase, β-glucosidase, exoglucanase, and xylanase were 1.63 IU/mL, 1.28 IU/mL, 0.08 IU/mL, and 47.93 IU/mL, respectively). Enzyme-treated substrate of Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Kuila et al [106,107] explored the use of a laccase from Pleurotus sp. to treat milled materials from Indian Thorny bamboo (Bambusa bambos) and Spanish flag (Lantana camara).…”
Section: Delignification By Laccase Alonementioning
confidence: 99%
See 1 more Smart Citation
“…Kuila et al [106,107] explored the use of a laccase from Pleurotus sp. to treat milled materials from Indian Thorny bamboo (Bambusa bambos) and Spanish flag (Lantana camara).…”
Section: Delignification By Laccase Alonementioning
confidence: 99%
“…Better accessibility of hydrolytic enzymes [106,107] Milled material from Ricinus communis Pleurotus sp.…”
Section: Pretreated Materials Laccase Treatment Effects Observed Benefmentioning
confidence: 99%
“…In comparison with the solid-state fermentation, enzymatic delignification processes demand less incubation time. Kuila et al (2011) reported a maximum delignification of Bambusa bambos of 84% using laccase from Pleurotus sp. at 400 IU/mL after 8h of incubation.…”
Section: Biological Treatmentsmentioning
confidence: 99%
“…The enzymatic mechanism is substrate specific which results in wastage of material, increased reaction rates, and improved delignification efficiency . There are two ways to perform enzymatic delignification: (1) a cell culture supernatant is used which has distinct and discrete ligninolytic activities, and (2) a sole purified and concentrated enzyme solution is used . During the use of ligninolytic enzymes, no nutrient supplementation is required, and these enzymes can work wide ranges of pH (pH 3‐8) and temperatures (25°C‐80°C) .…”
Section: Organic Solventsmentioning
confidence: 99%
“…Ligninolytic enzymes as shown in Table are successfully used for a number of industrial applications, such as, organic compound manufacturing, polymer reformation, and removal of environmental toxins . The use of laccases to remove lignin was successfully applied to improve enzymatic hydrolysis . In the case of laccase enzyme, a suitable redox mediator must be present to stabilize in its redox states, and it should not inhibit the catalytic activity .…”
Section: Organic Solventsmentioning
confidence: 99%